Realizing IR theories by projections in the UV - Fabian Klos; Daniel Roggenkamp (Journal of High Energy Physics)
Abstract We show how (topologically twisted) quantum field theories in the IR of bulk RG flows can be represented within the respective UV theories by means of codimenion- one projection defects. Indeed, from this perspective, RG flows of bulk theories can be described in terms of RG flows of the codimension-one identity defect in the fixed UV bulk theory. We illustrate this in the example of RG flows between supersymmetric Landau- Ginzburg orbifold models, for which the respective defects can be described in terms of matrix factorizations.